2010
DOI: 10.3109/10673229.2010.493744
|View full text |Cite
|
Sign up to set email alerts
|

Panic Disorder Respiratory Subtype: Psychopathology, Laboratory Challenge Tests, and Response to Treatment

Abstract: Some characteristics, such as the increased sensitivity to CO(2) and the higher familial history of PD, clearly distinguish the RS from the non-RS. Nevertheless, there are also controversial findings. More studies are needed to determine the validity of the RS subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 76 publications
1
49
0
2
Order By: Relevance
“…There were also conflicting findings regarding the duration of the illness 5,10 . High prevalence of respiratory symptoms was found in patients with nocturnal PAs or traumatic suffocation history 3 .…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…There were also conflicting findings regarding the duration of the illness 5,10 . High prevalence of respiratory symptoms was found in patients with nocturnal PAs or traumatic suffocation history 3 .…”
Section: Introductionmentioning
confidence: 97%
“…As a response to these concerns, alternative classification schemes have been devised 2 . Several studies indicated that PD patients with prominent respiratory symptoms may represent a distinct subtype of this disorder 3 . High rates of alcohol 4 and cigarette 5 use have been found in respiratory subtype patients.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations